Women (Under) Representation in Popular Culture - Jankauskaitė, Margarita (Sociologija. Mintis ir veiksmas, 2004)
The article continues the Lithuanian academic discourse and centers on the analysis of imagery that make up a concurrent part of modern mass culture and form codes of symbolic gender representation. Women’s representation strategies that make possible or, on the contrary, impossible the representation of women as subjects in the mass media are approached from the point of view of psychoanalysis, gender theory, mass media and cultural studies. The author focuses on the codes of “everyday pornography”, i.e., the naturalization of gender hierarchy, objectification of woman’s image, erotization of violence, and silencing of women, that are deeply rooted in the Lithuanian mass culture. She also analyses visual strategies that reinforce masculine hegemony and links their deconstruction with the critical evaluation of heterosexual imperative that supports the normative gender system.